Effects of late-night training on "slow-wave sleep episode" and hour-by-hour-derived nocturnal cardiac autonomic activity in female soccer players - Costa, J. A.; Brito, J.; Nakamura, F. Y.; Oliveira, E. M.; Rebelo, A. N. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess the sensitivity of nocturnal heart-rate-variability-monitoring methods to the effects of late-night soccer training sessions in female athletes. Methods: Eleven female soccer players competing in the first division of the Portuguese soccer league wore heart-rate monitors during sleep at night throughout a 1-wk competitive in-season microcycle, after late-night training sessions (n=3) and rest days (n=3). Heart rate variability was analyzed through "slow-wave sleep episode" (10-min duration) and "hour by hour" (all the RR intervals recorded throughout the hours of sleep). Training load was quantified by session rating of perceived exertion (281.8 [117.9] to 369.0 [111.7] arbitrary units [a.u.]) and training impulse (77.5 [36.5] to 110.8 [31.6] a.u.), added to subjective well-being ratings (Hopper index=11.6 [4.4] to 12.8 [3.2] a.u.). These variables were compared between training and rest days using repeated-measures analysis of variance. Results: The log-transformed slow-wave sleep-episode cardiac autonomic activity (lnRMSSD [natural logarithm of the square root of the mean of the sum of the squares of differences between adjacent normal RR intervals] varying between 3.92 [0.57] and 4.20 [0.60] Eta2p =.16 p2=.16; 95% confidence interval, .01-.26), lnHF (natural logarithm of high frequency), lnLF (natural logarithm of low frequency), lnSD1 (natural logarithm of short-term beat-to-beat variability), and lnSD2 (natural logarithm of long-term beat-to-beat variability), and the nontransformed LF/HF were not different among night-training session days and rest days (P>.05). Considering the hour-by-hour method (lnRMSSD varying between 4.05 [0.35] and 4.33 [0.32] Eta2p =.46 p2=.46 ; 95% confidence interval, .26-.52), lnHF, lnLF, lnSD1, and lnSD2 and the nontransformed LF/HF were not different among night-training session days and rest days (P>.05). Conclusion: Late-night soccer training does not seem to affect nocturnal slow-wave sleep-episode and hour-by-hour heart-rate-variability indices in highly trained athletes.